TСУТНІСТЬ ПЕДАГОГІЧНОЇ КУЛЬТУРИ ЯК СУСПІЛЬНО-ІСТОРИЧНОГО ЯВИЩА (Педагогіка вищої та середньої школи, 2007)
The system of pedagogical culture as a summary of structural and functional components that show variety of connections and interrelations between them is scientifically grounded. Author of article considers the essence of concept «pedagogical culture» in account the modern priorities of education. Thai has allowed to the author to make the generalization necessary for carrying out of the further research work.